Graphene Oxide-PES-Based Mixed Matrix Membranes for Controllable Antibacterial Activity against Salmonella typhi and Water Treatment. (18th November 2018) - Bhatti, Haleema Tariq; Ahmad, Nasir M.; Khan Niazi, Muhammad Bilal; Ur Rehman Alvi, Muhammad Azeem; Ahmad, Naveed; Anwar, Muhammad Nabeel; Cheema, Waqas; Tariq, Sheraz; Batool, Mehwish; Aman, Zaeem; Janjua, Hussnain A.; Khan, Asim Laeeq; et al.
Abstract : The present work is focused on preparation, characterization, and antibacterial activity evaluation of graphene oxide/polyethersulfone mixed matrix filtration membranes. Graphene oxide (GO) was synthesized via improved Hummer's method and characterized by XRD, FTIR, and SEM. FT-IR spectra showed the presence of carboxylic acid and hydroxyl groups on GO nanosheets. Different concentrations of the synthesized GO at 0.25, 0.5, and 1.0 wt. % were incorporated in polyethersulfone (PES) matrix via phase inversion method to fabricate GO-PES membranes. Increasing porosity and formation of wider, finger-like channels were observed with increased GO concentrations relative to pristine membranes as evident from scanning electron microscopy (SEM) micrographs of the fabricated membranes. However, membranes prepared with 1 wt. % GO appear to contain aggregation and narrowing of pore morphology. GO-incorporated membranes demonstrated enhanced flux, water-retaining capacities, and wettability as compared to pristine PES membranes. Shake flask and colony counting methods were employed to carry out antibacterial testing of synthesized GO and fabricated GO-PES membranes against Salmonella typhi ( S. typhi )—a gram-negative bacteria present in water that is known as causative agent of typhoid. Synthesized GO showed significant reduction up to 70.8% in S. typhi cell count. In the case of fabricated membranes, variable concentrations of GO are observed to significantly influence the percentage viability of S. typhi, with reduction percentages observed at 41, 60, and 69% for 0.25, 0.5, and 1.0 wt. % GO-incorporated membranes relative to 17% in the case of pristine PES membranes. The results indicate a good potential for applying GO/PES composite membranes for water filtration application.